2017
DOI: 10.1053/j.gastro.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β Superfamily Signaling in Development of Colorectal Cancer

Abstract: Transforming growth factor (TGF)-β cytokines signal via a complex network of pathways to regulate proliferation, differentiation, adhesion, migration, and other functions in many cell types. A high percentage of colorectal tumors contain mutations that disrupt TGF-β family member signaling. We review how TGF-β family member signaling is altered during development of colorectal cancer, models of study, interaction of pathways, and potential therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 185 publications
3
154
0
2
Order By: Relevance
“…Increasing evidence has suggested that signaling pathways such as WNT/β-catenin and TGFβ/SMAD pathways may be involved in modulating tumorigenesis [33, 34]. Among these pathways, activation of TGFβ/SMAD plays an important role in enhancing the EMT to remodel the prometastasis phenotype [11], and SNAIL family members are regulated by the TGFβ/SMAD signaling pathway [22]. Thus, we confirmed the expression of proteins critical in the TGFβ/SMAD pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence has suggested that signaling pathways such as WNT/β-catenin and TGFβ/SMAD pathways may be involved in modulating tumorigenesis [33, 34]. Among these pathways, activation of TGFβ/SMAD plays an important role in enhancing the EMT to remodel the prometastasis phenotype [11], and SNAIL family members are regulated by the TGFβ/SMAD signaling pathway [22]. Thus, we confirmed the expression of proteins critical in the TGFβ/SMAD pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several transcriptional factors strongly repress CDH1 transcription such as members of Snail, Zeb, and basic-helix-loop-helix (bHLH) families [22]. The TGFβ/SMAD signaling pathway plays an important role in a complicated signaling network, which coordinates the expression of Slug, Zeb, and bHLH families to promote tumor progression and enhance the EMT [11]. However, the detailed mechanisms underlying the EMT are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFBR1*6A, a common allele located at exon 1 of the TGFBR1 gene, has been reported to act as a low-penetrance tumor-susceptibility allele in human colorectal cancer cell lines. It is also less effective at transducing TGF-β signaling compared with the TGFBR1*9A wild type (10). Functional studies have demonstrated that the TGFBR1*6A allele is associated with an increased risk of various different malignancies, including breast cancer and osteosarcoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…Two major physiologic inhibitors are known, the competitive antagonist inhibin 9 and the specific ligand trap follistatin 10,11 . First described as a reproductive hormone upstream of follicle-stimulating hormone (FSH) 12 , subsequent studies showed substantial roles in such diverse contexts as embryogenesis 13 , cancer 8,14,15 , and inflammation 16 . In inflammation, activin has been reported to have both pro-and anti-inflammatory functions ex vivo, resulting in either up-or down-regulation of a number of key inflammatory cytokines, such as IL-6, IL-1-β or IL10 in a spectrum of human and murine cell types [17][18][19][20] .…”
mentioning
confidence: 99%